Penerapan Asas Keseimbangan terhadap Perjanjian Promosi antara Influencer dan Pemilik Bisnis dalam Perspektif Hukum Perdata - Muhammad Rivaldi Maulana; Saim Aksinuddin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The acceleration of the digital economy has popularized endorsement practices that often operate without adequate legal certainty. This legal study examines the validity of contracts and the implications of default through the lens of Commutative Justice Theory. The findings show that although legally valid electronically, contracts are vulnerable to cancellation due to issues surrounding the competence of underage influencers. Furthermore, breach of contract has been proven to distort the equality of exchange value. Therefore, this study recommends reconstructing contracts based on the Principle of Balance through a mechanism of gradual payment and data transparency in order to restore substantive contractual justice for the parties involved.